2015
DOI: 10.1590/s1806-37132015000000027
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of obstructive sleep apnea in patients undergoing pre-operative evaluation for bariatric surgery and referred to a sleep laboratory for polysomnography

Abstract: Objective: To identify the main predictive factors for obtaining a diagnosis of obstructive sleep apnea (OSA) in patients awaiting bariatric surgery. Methods: Retrospective study of consecutive patients undergoing pre-operative evaluation for bariatric surgery and referred for in-laboratory polysomnography. Eight variables were evaluated: sex, age, neck circumference (NC), BMI, Epworth Sleepiness Scale (ESS) score, snoring, observed apnea, and hypertension. We employed ROC curve analysis to determine the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“… 145 Evidence from the population with obesity may merit consideration in this context, given the close association to OSA, 146 reflected in the substantial OSA prevalence of ≤90% in male bariatric patients. 147 , 148 Notably, there is significant overlap between obesity and OSA with regard to challenges in general anesthesia because of altered cardiorespiratory physiology, including decreased functional residual capacity, upper airway obstruction, and the propensity to hypoxemia in perioperative settings. 149 , 150 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
“… 145 Evidence from the population with obesity may merit consideration in this context, given the close association to OSA, 146 reflected in the substantial OSA prevalence of ≤90% in male bariatric patients. 147 , 148 Notably, there is significant overlap between obesity and OSA with regard to challenges in general anesthesia because of altered cardiorespiratory physiology, including decreased functional residual capacity, upper airway obstruction, and the propensity to hypoxemia in perioperative settings. 149 , 150 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
“…The estimated prevalence of moderate-to-severe sleep-disordered breathing (SDB) ranges from 10 to 17% among men and from 3 to 9% among women [1], likely reflecting the increase in obesity rates and aging of the population [2,3]. In certain risk groups, such as patients undergoing pre-operative evaluation for bariatric surgery [4] or resistant hypertension [5], the prevalence can reach more than 70%. In patients with OSA, the recurrent snoring and associated local mechanical trauma to the airway along with the recurrent upper airway collapse and intermittent hypoxia-re-oxygenation episodes lead to release of inflammatory mediators, leading to both local upper airway and systemic inflammation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that to predict sleep apnea syndrome, threshold values for BMI, neck circumference, and age are >42 kg/m 2 , 42 cm, and 37 years, respectively. [3] The patient in this case scored above the 3 threshold values in the STOP-BANG scoring system, but had no diagnosis of sleep apnea syndrome. Nonetheless, the risk was assessed as high.…”
Section: Discussionmentioning
confidence: 79%